(untitled) - Christensen, Clayton M. (Boston, Massachusetts, 2013)
A seminal work by bestselling author Clayton M. Christensen. In his international bestseller The Innovator's Dilemma, Clayton M. Christensen exposed this crushing paradox behind the failure of many industry leaders: by placing too much focus on pleasing their most profitable customers, these firms actually paved the way for their own demise by ignoring the disruptive technologies that aggressively evolved to displace them. In The Innovator's Solution, Christensen and coauthor Michael E. Raynor help all companies understand how to become disruptors themselves. Clay Christensen (author of the award-winning Harvard Business Review article, "How Will You Measure Your Life?") and Raynor not only reveal that innovation is more predictable than most managers have come to believe, they also provide helpful advice on the business decisions crucial to truly disruptive growth. Citing in-depth research and theories tested in hundreds of companies across many industries, the authors identify the processes that create successful innovation--and they show managers how to tailor their strategies to the changing circumstances of a dynamic world. The Innovator's Solution is an important addition to any innovation library
Keywords: Công nghệ đột phá,Disruptive technologies